Baseline and changes in inflammatory parameters for patients with EGFR‐mutated NSCLC treated with afatinib - Zi‐Ting Chang; Ping‐Chih Hsu; How‐Wen Ko; John Wen‐Cheng Chang; Chen‐Te Wu; Chen‐Yang Huang; Ching‐Fu Chang; Chih‐Hsi Scott Kuo; Cheng‐Ta Yang; Chiao‐En Wu (Thoracic Cancer, 2025)
Abstract Background This study investigated the relationship between inflammatory biomarkers (lymphocyte ratio [NLR], monocyte‐to‐lymphocyte ratio [MLR], and platelet‐to‐lymphocyte ratio [PLR]) and the treatment outcomes of patients with non‐small cell lung cancer (NSCLC) treated with afatinib. Methods The patients with NSCLC treated with afatinib between June 2014 and February 2018 were retrospectively reviewed. Their inflammatory biomarkers and clinical outcomes (progression‐free survival [PFS] and tumor response) were explored using univariate and multivariate analyses. Results Among 325 patients, those with an NLR >2.18, MLR >0.19, and PLR >177.73 had significantly worse PFS than those with lower values. After adjusting for performance status, stage, and liver metastasis, the PFS was still unfavorable for a baseline NLR >2.18, MLR >0.19, or PLR > 177.73. Among 188 patients with paired inflammatory values, those whose NLR decreased by >29.5%, MLR decreased by >57.9%, and PLR increased by <18.8% had significantly better PFS. After adjusting for performance status, stage, and liver metastasis, the PFS was significantly unfavorable for an NLR decrease of <29.5% and MLR decrease of <57.9%. Among the patients with tumor response, NLR, MLR, and PLR significantly decreased after treatment (all p < 0.05). Conclusions Our study presented the NLR, MLR, and PLR as prognostic factors for patients with NSCLC treated with afatinib. Further investigation into these markers representing the tumor microenvironment and their association with cancer status is crucial for evaluating prognosis and clinical outcomes in patients with NSCLC.